Defying death struggles against imperialism and feudalism - Gupta, Maya; Gupta, Amit Kumar 1936- (Tulika Books, 2020)
Predominantly on the role of Indian freedom fighters armed resistance against British imperialism during 1857-1947
Keywords: Geschichte 1857-1950; Unabhängigkeitsbewegung; Britisch-Indien; India / Politics and government / 1857-1919; India / Politics and government / 1919-1947; Nationalism / India / History; Nationalism; Politics and government; India; 1857-1947; History; Aufsatzsammlung